2017 25th European Signal Processing Conference (EUSIPCO) 2017
DOI: 10.23919/eusipco.2017.8081470
|View full text |Cite
|
Sign up to set email alerts
|

Topographical pattern analysis using wavelet based coherence connectivity estimation in the distinction of meditation and non-meditation EEG

Abstract: Abstract-Classification of EEG signal involved in a particular cognitive activity has found many application in brain-computer interface (BCI). In specific, use of classification algorithms to highly multivariate non-stationary recordings like EEG is a challenging and promising task. This study investigated two substantial novelty of the topics, (1) Distinction between meditation (Kriya Yoga) and non-meditation state allied EEG, (2) Characterization of the underlying mechanism of cognitive process that is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In 2017, Shaw et al conducted an investigation into the brain connectivity of meditators and non-meditators utilizing topographic wavelet coherence (Shaw & Routray, 2017). The study revealed a significant difference in topographical connectivity between the two groups, suggesting that meditators exhibit a distinct degree of synchrony among different brain regions during both meditation and the resting state.…”
Section: Brain Network Analysismentioning
confidence: 99%
“…In 2017, Shaw et al conducted an investigation into the brain connectivity of meditators and non-meditators utilizing topographic wavelet coherence (Shaw & Routray, 2017). The study revealed a significant difference in topographical connectivity between the two groups, suggesting that meditators exhibit a distinct degree of synchrony among different brain regions during both meditation and the resting state.…”
Section: Brain Network Analysismentioning
confidence: 99%